AB1042 Patient Beliefs Regarding Associations between Weather and Pain; An Analysis of Enrolment Questionnaires within "Cloudy with A Chance of Pain". (15th July 2016) - Patel, R.; Sergeant, J.; McBeth, J.; Schultz, D.; Sanders, C.; Cook, L.; Ainsworth, J.; Dixon, W.
Abstract : Background: The association between the weather and chronic pain is complex and largely undetermined. More than 80% of patients believe in an association between weather and pain. However, beliefs vary about which weather variable (e.g. temperature, atmospheric pressure) influences pain, with possible differences across pain disorders. Objectives: To describe participants' beliefs about an association between weather and pain at the time of enrolment to a national smartphone study entitled "Cloudy with a Chance of Pain", stratified by self-reported diagnosis. Methods: Participants in the UK aged 17 years or older, with access to a smartphone and who had arthritis or other chronic pain for at least 3 months were recruited to "Cloudy with a Chance of Pain". Participants completed an 8 point enrolment questionnaire which included two questions about their beliefs: 1) Belief strength: On a scale of 0–10, how likely do you think weather is associated with pain? 2) Belief type: If you think there is a possible association, which weather condition(s) affect your pain the most? Both questions offered categorical response options. In question 2, participants were permitted to select multiple categories and a "free text" option was also offered. We present a descriptive analysis of the categorical data and sub-analyses of differential beliefs by age (above/below 50yrs), gender and self-reported diagnosis. Results are reported as median (IQR) or number (%). Mann-Whitney U-Test and Fisher's exact test were used for statistical analysis. Within Table 1, significant associations (p<0.05) are denoted by bold text. Results: 5, 282 enrolment questionnaires were included in analysis. Median belief strength was 7 (5–9). 8% reported a belief strength of 4 or less. Participants most commonly believed that "damp/rain" affected their symptoms (72%). When compared to the total study population, those with fibromyalgia, chronic headache and neuropathic pain more frequently believed that changes in temperature and pressure correlated with pain. Indeed, participants with fibromyalgia and neuropathic pain more commonly reported belief in an association between all aspects of weather and pain when compared to the total study population. Table 1 summarises belief strength and belief type by gender, age and underlying diagnosis. Conclusions: Most participants strongly believed in an association between weather and pain. Participants most commonly believed that damp/rain affected their pain. Specific beliefs vary between participants and between diagnostic groups, perhaps reflecting different causal pathways in these conditions. Acknowledgement: Arthritis Research UK and uMotif Ltd. Disclosure of Interest: None declared